Isolation, identification, and mechanism analysis of plant growth-promoting rhizobacteria in tobacco - Jiang, Chuandong; Peng, Fuyu; Zhang, Li; Zhang, Yuqin; Wang, Jie; Li, Junmin; Cui, Binghui; Cao, Changdai; Wang, Chengqiang; Qin, Yunlei; Wang, Ran; Zhao, Zongpeng; et al. (Frontiers in Microbiology, 2024)
Plant growth, crop yield, and pest and disease control are enhanced by PGPR (Plant growth promoting rhizobacteria), which are beneficial microorganisms found in a close symbiosis with plant roots. Phytohormones are secreted, nutrient uptake is improved, and soil properties along with the microbiological environment are regulated by these microorganisms, making them a significant focus in agricultural research. In this study, the highly efficient PGPR, Trichoderma harzianum, designated T1, was successfully isolated from tobacco inter-root soil. Following the application of T1, significant improvements were observed in the height, leaf length, and width of tobacco plants. Furthermore, the physical and chemical properties of the soil were notably enhanced, including a 26.26% increase in phosphorus availability. Additionally, the activities of key soil enzymes such as sucrase, catalase, and urease were significantly increased, indicating improved soil health and fertility. Comprehensive joint microbiomics and macrogenomics analyses revealed a substantial rise in the populations of beneficial soil microorganisms and an enhancement in metabolic pathways, including amino acid metabolism, synthesis, and production of secondary metabolites. These increase in beneficial microorganisms and the enhancement of their metabolic functions are crucial for plant growth and soil fertility. This study provides valuable references for the development of innovative microbial fertilizers and offers programs for the sustainable development of modern agriculture.